Sex and recombination in aflatoxigenic Aspergilli: global implications - Moore, Geromy G. (Frontiers in Microbiology, 2014)
For most of the half century that aflatoxigenic species have been intensively studied, these molds were known only to reproduce asexually, with parasexuality found only in the laboratory between certain mutant strains. Therefore, the fairly recent discovery of their sexual (teleomorphic) states creates a new wrinkle in our understanding of the field behavior of these agriculturally significant fungi. Sex within populations of these fungi, and attendant genetic recombination, eventually may create difficulties for their control; and subsequently for the protection of important human and animal food supplies. Moreover, if fungal sex is a form of response to ecological and environmental stressors, then perhaps human influence and climate change could accelerate this phenomenon. This article will explore scientific research into sexuality and recombination in aflatoxigenic Aspergillus species; the potential impacts these phenomena could have on a popular method of pre-harvest prevention of aflatoxin contamination (i.e., use of non-aflatoxigenic A. flavus for biocontrol); and the outlook for maintaining control of aflatoxin contamination in an era of changing global climate.